Photo-assisted generation of phospholipid polymer substrates for regiospecific protein conjugation and control of cell adhesion. (August 2016) - Tanaka, Masako; Iwasaki, Yasuhiko
Graphical abstract: Abstract: Novel photo-reactive phospholipid polymers were synthesized for use in the preparation of nonfouling surfaces with protein conjugation capacity. Poly[2-methacryloyloxyethyl phosphorylcholine (MPC)- ran - N -methacryloyl-(l )-tyrosinemethylester (MAT)] (P(MPC/MAT)) was synthesized by conventional radical polymerization, with the MAT units capable of being oxidized by 254 nm UV irradiation. Because of this photo-oxidation, active species such as catechol and quinone were alternately generated in the copolymer. A silicon wafer was subjected to surface modification through spin coating of P(MPC/MAT) from an aqueous solution for use as a model substrate. The surface was then irradiated several times with UV light. The thickness of the polymer layers formed on the Si wafers was influenced by various parameters such as polymer concentration, UV irradiation time, and composition of the MAT units in P(MPC/MAT). Oxidized MAT units were advantageous not only for polymer adhesion to a solid surface but also for protein conjugation with the adhered polymers. The amount of protein immobilized on UV-irradiated P(MPC/MAT) was dependent on the composition of the MAT units in the polymer. Furthermore, it was confirmed that protein immobilization on the polymer occurred through the oxidized MAT units because the protein adsorption was significantly reduced upon blocking these units through pretreatment with glycine. Conjugation of regiospecific protein could also be achieved through the use of a photomask. In addition, nonspecific protein adsorption was reduced on the non-irradiated regions whose surface was covered with physisorbed P(MPC/MAT). Therefore, P(MPC/MAT) can be used in the preparation of nonfouling substrates, which enable micrometer-sized manipulation of proteins through photo-irradiation. Function of proteins immobilized on MPC copolymers was also confirmed by cell adhesion test. As such, photo-reactive MPC copolymers are suitable for performing controlled protein conjugation and preparing polymer–protein hybrid platforms for use in biomedical and diagnostic devices. Statement of Significance: Novel photo-reactive phospholipid polymers have been synthesized for immobilization on solid surfaces and regiospecific protein conjugation. Tyrosine residues embedded in 2-methacryloyloxyethyl phosphorylcholine (MPC) copolymers could be photo-oxidized, resulting in polymers able to form layers on a solid surface and conjugate with proteins. Moreover, nonspecific biofouling on the surface significantly reduced when the oxidized tyrosine units in the polymer layers were blocked. Upon UV irradiation through a photomask, the UV-exposed tyrosine units were selectively oxidized, forming the only specific regions in which protein conjugation could occur.